Pengaruh Perceived Threat dan Perceived Efficacy terhadap Intention to Comply Preventive Behavior dalam Pemasaran Sosial Covid-19 - Baiq Fahmi Ilmiati; Baiq Handayani Rinuastuti; Lalu Edy Herman Mulyono; Lalu M. Furkan (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2022)
Social marketing is becoming an urgent issue during pandemic era to control covid 19 virus. The research aim is to clarify factors affecting precventive actions of covid-19 among society from perspective of fear appeal. The research is a quantitative research with associative and causal hypotheses. Proportionate stratified random sampling was applied and distributed into 6 main island with 100 sample of respondent all over Indonesia. They are Java, Sumatra, Sulawesi, Kalimantan, Bali-Nusa tenggara, and Maluku-Papua. Online survey using google form was applied on data collection. Data was analyzed by SEM-PLS with Smart PLS software. Based on the research finding, we found perceived threat and perceived efficacy have positive and significant impact on the intention to comply for the covid-19 preventive behaviour.